2002
DOI: 10.3358/shokueishi.43.62
|View full text |Cite
|
Sign up to set email alerts
|

Oxytetracycline and Oxolinic Acid Residues in Kuruma Prawn(Penaeus japonicus) and the Effect of Cooking Procedures on the Residues.

Abstract: Tissue distribution and residue depletion of oxytetracycline (OTC) and oxolinic acid (OA) were studied in the kuruma prawn (Penaeus japonicus). The prawn were kept in tanks with recirculated artificial seawater at a salinity of 22ῐ23̮. The water temperature was maintained at 25̮. The average body weight was 22.94.9 g for OTC and 22.53.6 g for OA. The drug was mixed with the diet and orally administered through a catheter to the prawn. The doses of OTC and OA, respectively, were 50 mg/kg body weight. At each sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
(2 reference statements)
2
8
1
Order By: Relevance
“…In addition, OTC residues in shell were considerably thermostable. Similar findings have been reported for OTC residues in muscle and shell from P. japonicus and P. monodon (Uno 2002;Uno et al 2006). On the contrary, OTC residues in shell were considerably reduced ([80%) by the acid treatment because the Ca-tetracycline chelates were released from shell into hydrochloric acid solution.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, OTC residues in shell were considerably thermostable. Similar findings have been reported for OTC residues in muscle and shell from P. japonicus and P. monodon (Uno 2002;Uno et al 2006). On the contrary, OTC residues in shell were considerably reduced ([80%) by the acid treatment because the Ca-tetracycline chelates were released from shell into hydrochloric acid solution.…”
Section: Discussionsupporting
confidence: 89%
“…On the contrary, OTC was accumulated and retained strongly in the shell. In our previous study, OTC accumulated in the shell tissue of P. japonicus (Uno 2002) and P. monodon (Uno et al 2006) because Ca-tetracycline chelates were a considerable stabilizing factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differently to OTC, there is not a group in the structure of SM 2 that is able to chelate calcium. However, previous studies reported that OTC accumulated in the shell of P. japonicus and P. monodon because Ca‐tetracycline chelates were a considerable stabilizing factor (Uno ; Uno et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies concerning the pharmacokinetics (PK) of OXA have been conducted in numerous cold‐water fish species, including Atlantic salmon ( Salmo salar ) (, & Smith, 2), rainbow trout ( Oncorhynchus mykiss ) (Björklund, Eriksson, & Bylund, ) and Atlantic halibut ( Hippoglossus hippoglossus ) (Samuelsen & Ervik, ). However, most of these studies were conducted with fish species and less information has been obtained for the PK of antimicrobials in crustaceans (Uno, ). In addition, compared with fish, shrimp have completely different anatomies of the digestive tract and hepatopancreas (Dall, ) and compared with vertebrates, these animals have slower metabolisms and pharmaceutical excretion (Ceccaldi, ).…”
Section: Introductionmentioning
confidence: 99%